2021
DOI: 10.1039/d0fo02462g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of industrial processing and storage procedures on oxysterols in milk and milk products

Abstract: Oxysterols are products of enzymatic and/or chemical cholesterol oxidation. Their measurement during and after a milk production chain could represent a useful tool to monitor and increase the commercial and nutritional value of milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 45 publications
4
27
0
Order By: Relevance
“…Also Risso et al 34 analysed the 7β-HC changes in milk powder during storage. They found that the content of 7β-HC reached 0.265 µg g −1 cholesterol and 0.569.83 µg g −1 in skim milk powder and whole milk powder, respectively, after 12 months, and these amounts are potentially toxic in several in vitro and in vivo experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Also Risso et al 34 analysed the 7β-HC changes in milk powder during storage. They found that the content of 7β-HC reached 0.265 µg g −1 cholesterol and 0.569.83 µg g −1 in skim milk powder and whole milk powder, respectively, after 12 months, and these amounts are potentially toxic in several in vitro and in vivo experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on the quantification of oxysterols in a broad range of dairy ingredients and products including, but not limited to, dairy and cheese spreads, butter, butter oil, cheese (both aged and fresh, whole and grated), milk (both raw and processed, liquid, powdered, condensed, and evaporated), buttermilk, infant formula, and yogurt [ [114] , [115] , [116] , [117] , [118] , [119] ]. In these kinds of products, total non-enzymatic (or partially enzymatic) oxysterols were found to be in the broad range of 0–366 μg/g, depending on several factors such as the type of analyzed matrix, the age of the tested product, the processing conditions employed.…”
Section: Food Industrymentioning
confidence: 99%
“…While most of the studies present in literature have quantified 7βOHC and 7KC, fewer studies analyzed the broader array of these compounds together, such as 7αOHC, α-epoxy, β-epoxy, 25OHC, 27OHC and triol ( Table 3 ). Regarding enzymatic oxysterols, to our knowledge so far only a single study recorded and quantified the presence of 27OHC in dairy and dairy products [ 117 ].…”
Section: Food Industrymentioning
confidence: 99%
See 2 more Smart Citations